Blood novels : gender, caste, and race in Spanish realism - Chang, Julia H. (Toronto Iberic ;, 2022)
"In the late nineteenth century, Spain's most prominent writers--Juan Valera, Leopoldo Alas, and Benito Pérez Galdós--made blood a crucial feature of their fiction. Blood Novels examines the cultural and literary significance of blood, unsettling the dominant assumption of the period that blood no longer plays a decisive role in social hierarchies. By examining fictional works through the rubric of "blood novels," Julia H. Chang identifies a shared fascination with blood that probes the limits of realism through blood's dual nature of matter and metaphor. Situating the literature within broader cultural and theoretical debates, Blood Novels attends to the aesthetic contours of material blood and in particular how bleeding is inflected by gender, caste, and race. Critically engaging with feminist theory, theories of race and whiteness, literary criticism, and medical literature, this innovative study makes a case for treating blood not only as a critical analytic tool that sheds new light on Spanish realism but, more broadly, one that challenges our understanding of gendered and racialized embodiment in Spain."--